PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK - Sukirman Sukirman; Moch. Solikin (Jurnal Pendidikan Vokasi Otomotif, 2020)
This study implemented the Problem Based Learning learning model to increase the students’ activeness and learning outcomes in the conventional fuel system competency in class XI TKRA SMK Nasional Berbah. A Classroom Action Research (PTK) with Kurt Lewin's model was conducted, and the data were collected using observation, tests, and documentation. The indicator of the success of this study is if more than 75% of students are active and 75% of students reach the minimum score criteria (75). The participants of this study were 32 students of class XI. The results showed that the application of PBL able to increase the students’ activeness and learning outcomes on the competence to understand the conventional gasoline fuel system. This can be seen from: (1) an increase in positive activities (activities that support the implementation of the teaching and learning process) and a decrease in negative activities (activities that interfere with the implementation of the teaching and learning process) in each cycle. Positive activity in cycle I was 51% and cycle II was 76%; (2) there is an increase in the class average and students' learning completeness. The class average in cycle I was 71 and cycle II was 78. Meanwhile, students' learning completeness in cycle I was 43.75%, cycle II was 84.37%.